Development of porous MIL-101 derived catalyst application for green diesel production - Chang, He; Abdulkareem-Alsultan, G.; Taufiq-Yap, Y.H.; Mohd Izham, S.; Sivasangar, S. (Elsevier Ltd, 2024)
A novel three-dimensional MIL-101 derived porous carbon-based Ni-doped catalyst was synthesised via slow pyrolysis of Ni/MIL-101(Cr) precursor at 600 °C for 4 h. The catalytic activities were evaluated via one-pot hydrodeoxygenation (HDO) reactions by using palmitic acid (PA) as a model compound to produce green diesel within the range of a paraffinic hydrocarbon. The results show that Ni/P-MIL-101 exhibited excellent catalytic activity and recyclability in the HDO reaction of PA at a reaction temperature of 400 °C for 3 h under 3 MPa purified H2 pressure with 5 wt catalyst loading. The conversion of PA and hydrocarbon selectivity were found to be 100 with Ni loading > 8 wt on P-MIL-101. In addition, both 25 and 14 wt Ni/P-MIL-101 catalysts were able to recycle up to 7 and 15 times, respectively, and nearly 100 alkane yield was achieved. The unique properties of Ni/P-MIL-101 catalyst such as finely dispersed added Ni, abundant acid and basic sites, and the presence of Cr2O3 active sites from pyrolysed MIL-101 with its mesoporous structures play a synergetic role in obtaining a very efficient catalyst for hydrodeoxygenation reaction. It is worth mentioning that the catalyst has an excellent catalytic effect on different kinds of fatty acid (ester) raw materials. Therefore, this Ni/P-MIL-101 catalyst has good prospects and potential for industrial application in green diesel production.